Priming com ácido salicílico como estratégia de atenuação dos efeitos deletérios da salinidade em plântulas de arroz - Nobre, Geovane Damasceno (2024)
Salinity is an abiotic stress that affects plant growth and development, especially in arid and semi-arid regions. In the case of rice (Oryza sativa L.), the third most-produced cereal in the world, this condition can seriously compromise the germination and seedling establishment processes, which justifies the need to improve techniques aimed to increase its ability to acclimatize to salinity. As studies have shown that physiological conditioning can make crops more tolerant to environmental stresses. Hence, this study tested the hypothesis that seed priming with salicylic acid (SA) act to mitigate the harmful effects of salinity during the rice seedlings establishment by metabolic changes capable of favoring osmotic, ionic and redox homeostasis. The First, a screening evaluated SA at concentrations of 0, 0.125, 0.25, 0.5, 1.0, and 2.0 mM as a priming agent for rice seeds sown under saline conditions (80 mM NaCl). The treatments were composed by five replicates comprised by 50 seeds each. The germination parameters and seedling growth analysis selectedthe most suitable AS concentration for seed priming. The results showed that 2.0 mM concentration of SA promoted the highest values in the germination variables and, above all, in the seedling growth variables. Next, the second experiment consisted by four treatments comprising two concentrations of SA (0 and 2.0 mM) and two of NaCl (0 and 80 mM) arranged in a 2 x 2 factorial scheme conducted and a completely randomized design. Overall, salt stress negatively affected the ionic and redox balance of the seedlings. However, in those whose seeds had been previously SA-primed, there was an improvement in the K+ /Na+ ratio, in antioxidant response though catalase enzyme, and SA path via phenylalanine ammonia-lyase enzyme. Additionally, osmotic potential, electrolyte leakage, and malondialdehyde and hydrogen peroxide (H2O2) contents were also lower in these seedlings. The GC/MS technique quantified the endogenous SA content, which significantly increased in the seedlings from SA-primed seeds. Through metabolic profile analysis of the shoot and roots (metabolome) of seedlings, SA-priming favored, for example, an increase in the levels of proline and asparagine in the shoots , suggesting a possible improvement in osmotic adjustment and the toxicity generated by salinity. In addition, priming with SA caused increases in the relative levels of phenolic compounds, including quinic acid, caffeic acid, and quercetin, as well as ascorbic acid, which corroborate the redox state of seedlings. Finally, priming the seeds with 2.0 mM SA helped to mitigate the toxicity caused by salinity, causing metabolic changes favorable to maintaining the ionic, osmotic, and redox balance of the rice seedlings.